2019
DOI: 10.1186/s12887-019-1675-4
|View full text |Cite
|
Sign up to set email alerts
|

Prospective case control study of iron deficiency and the risk of febrile seizures in children in South Korea

Abstract: Background Febrile seizures are the most common type of seizure in the first 5 years of life, and many factors that increase seizure risk have been identified. This study was performed to examine the association between iron status and febrile seizures in children in South Korea. Methods A prospective unmatched case control study was performed in 63 cases of febrile seizures and 65 controls with febrile illness but no seizures. Results Serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
40
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 30 publications
11
40
1
1
Order By: Relevance
“…Additionally, Sharawat et al observed that RBC indices showed statistically significant lower mean Hb, MCV, and MCH and higher RDW values in cases compared to controls 35 . However, contrary to the findings of this study, Jang et al, observed no significant difference between the groups in terms of CBC parameters (all p-values >0.05) 22 . This could be due to low prevalence of IDA and improved nutritional status amongst South Korean children.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Additionally, Sharawat et al observed that RBC indices showed statistically significant lower mean Hb, MCV, and MCH and higher RDW values in cases compared to controls 35 . However, contrary to the findings of this study, Jang et al, observed no significant difference between the groups in terms of CBC parameters (all p-values >0.05) 22 . This could be due to low prevalence of IDA and improved nutritional status amongst South Korean children.…”
Section: Discussioncontrasting
confidence: 99%
“…This could be due to low prevalence of IDA and improved nutritional status amongst South Korean children. The findings of this study are in accordance with Jang et al who observed a significantly increased TIBC and significantly lower SI levels in cases, as compared to controls 22 . Sharif et al observed a significant difference between cases and controls in the mean SI (p-value = 0.028) and TIBC (p = 0.0001).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“… 12 , 13 Febrile seizures, breath-holding spells, and restless leg syndrome have also been shown to be much more prevalent in people with iron deficiency. 14 16 In adolescent and young adult females, isolated iron deficiency is associated with fatigue and cold intolerance that is relieved with appropriate oral iron therapy. 17 …”
Section: Introductionmentioning
confidence: 99%
“…Iron deficiency anemia is common in children in third world countries 1 . Almost one in three children suffers from iron deficiency (ID) due to poverty, lack of iron-rich foods, malabsorption or worm infestation.…”
Section: Introductionmentioning
confidence: 99%